Pengaruh Putusan Pailit Terhadap Tanggung Jawab Organ Suatu Perusahaan - Sardana, Layang; Ermini, Ermini; Suryati, Suryati (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
A bankruptcy to a company may result in a working relationship being ended or terminated by a person. Based on this there are often disputes between employers and workers. Disputes between the parties are usually caused by feelings of dissatisfaction. Employers provide policies that they think are good, but the workers in question have their own considerations and views so are not satisfied with the policy given. The purpose of this research is to find out the effect of bankruptcy rulings on a company's organ responsibilities. The type of legal research used in research is normative juridical research. The result of this research is that the effect of the bankruptcy statement has an impact on the Board of Directors and Commissioners described in Article 93 and Article 110 of Law No. 40 of 2007 on the Limited Liability Company which states that the board of directors and commissioners cannot be reappointed in such positions if within 5 years before his appointment has been declared bankrupt. This is reaffirmed in Article 95 and Article 112 of Law No. 40 of 2007 on Limited Liability Companies stating that appointments that do not meet the requirements are null and void from the moment a member of the Board of Directors or Board of Commissioners is aware of the requirement.